Effect of Temperature and Velocity of Drying Air on Kinetics, Quality and Energy Consumption in Drying Process of Rice Noodles - Kongkiattisak , Pisut; Songsermpong, Sirichai (Agriculture and Natural Resources, 2012)
The drying characteristics of rice noodles were observed at three levels of air drying temperature and two levels of average air drying velocity on the rice noodle surface. The results indicated that the temperature significantly affected the drying process while the velocity was not significant in the terminal stage of the drying process. The drying process for rice noodles occurred during the falling rate period. The effective moisture diffusivity increased at higher air drying temperatures and velocities. The TwoTerm model was the most appropriate of all the thin-layer drying equations to explain and predict the drying process of rice noodles. Drying at 85 °C and 0.30 m.s-1 can be applied in the production of dried rice noodles to reduce both the primary specific energy in the drying process and the cooking loss of rice noodles. Moreover, this condition resulted in a structure, textural quality and water absorption index which did not differ from other drying conditions.